Subcortical ischemic vascular disease and cognition. A systematic review - Gilberto Sousa Alves (Dementia & Neuropsychologia, 2008)
Subcortical Ischemic Vascular Disease (SIVD) is underdiagnosed. This review investigates the re-lationship among SIVD severity, cognitive status and neuroimaging markers. Methods: Cohort, cross-sectional and case control studies were searched on ISI, Medline, Scielo, PsychoInfo and LILACS databases published between 1995 and 2006. Results: The most impaired cognitive domains were executive, attentional and memory retrieval mechanisms. These cognitive features were frequently associated to White Matter Lesions (WML). Conclusions: WML is an independent factor in cognitive decline. However, the threshold for this impact is not yet clearly established .